IgY Anti-N SARS CoV2-Conjugated Gold Nanoparticles Production for Lateral Flow Biosensor-Based Diagnostics - Idar, Idar; Yusuf, Muhammad; Al Anshori, Jamaludin; Subroto, Toto (Trends in Sciences, 2025)
Although the number of COVID-19 cases is decreasing, the virus continues circulating, necessitating ongoing detection efforts. This is particularly important because COVID-19 symptoms like fever can resemble those of other tropical diseases like dengue fever. Lateral Flow Strip Biosensors (LFSB) offer a rapid and cost-effective testing method to address this issue. A crucial factor influencing the sensitivity and specificity of LFSB is the conjugate, which consists of a detection antibody and a visualization agent. Anti-N-SARS-CoV-2 IgY can be utilized as the detection antibody. This antibody was produced by immunizing chickens with a stable antigen derived from the SARS-CoV-2 virus, specifically the SARS-CoV-2 nucleocapsid protein (N-SARS-CoV-2). Gold nanoparticles serve as the visualization agent, enabling visual readings of the LFSB without additional equipment. The size of the gold nanoparticles affects their surface area and the resulting color, affecting the sensitivity of the LFSB. While various sizes of gold nanoparticles are available commercially, they tend to be quite costly, affecting the production expenses of the LFSB. Therefore, this study aims to develop LFSB conjugates for SARS-CoV-2 detection by synthesizing gold nanoparticles of different sizes and conjugating them with IgY anti-N-SARS-CoV-2. The gold nanoparticles were synthesized using the Turkevich-Seed Growth method, which allows for variations in size within a single synthesis process and uses non-toxic materials. The synthesized gold nanoparticles were characterized using a spectrophotometer, and their sizes were analyzed with a particle size analyzer. Subsequently, they were conjugated with anti-N-SARS-CoV-2 IgY via a passive conjugation method. The conjugates were characterized based on maximum wavelength shifts, and their aggregation parameters and functionality were tested using a half-strip spot test. This research demonstrates that gold nanoparticles of 63.9 nm are the most suitable for conjugation with anti-N-SARS-CoV-2 IgY. HIGHLIGHTS Gold nanoparticles produced via the seed growth method demonstrated good stability after being stored for nearly a year at a temperature of 4 °C in a dark container. The synthesized gold nanoparticles remained stable in Trizma buffer at a pH 9. Gold nanoparticles obtained from each synthesis cycle using the seed growth method can serve as seeds for synthesizing larger gold nanoparticles. The half-strip spot test is the initial step in testing the sensitivity of conjugates. GRAPHICAL ABSTRACT